Distinct Contributions of the Peroxisome-Mitochondria Fission Machinery During Sexual Development of the Fungus Podospora anserina - Navarro-Espíndola, Raful; Takano-Rojas, Harumi; Suaste-Olmos, Fernando; Peraza-Reyes, Leonardo (Frontiers in Microbiology, 2020)
Mitochondria and peroxisomes are organelles whose activity is intimately associated and that play fundamental roles in development. In the model fungus Podospora anserina, peroxisomes and mitochondria are required for different stages of sexual development, and evidence indicates that their activity in this process is interrelated. Additionally, sexual development involves precise regulation of peroxisome assembly and dynamics. Peroxisomes and mitochondria share the proteins mediating their division. The dynamin-related protein Dnm1 (Drp1) along with its membrane receptors, like Fis1, drives this process. Here we demonstrate that peroxisome and mitochondrial fission in P. anserina depends on FIS1 and DNM1. We show that FIS1 and DNM1 elimination affects the dynamics of both organelles throughout sexual development in a developmental stage-dependent manner. Moreover, we discovered that the segregation of peroxisomes, but not mitochondria, is affected upon elimination of FIS1 or DNM1 during the division of somatic hyphae and at two central stages of sexual development—the differentiation of meiocytes (asci) and of meiotic-derived spores (ascospores). Furthermore, we found that FIS1 and DNM1 elimination results in delayed karyogamy and defective ascospore differentiation. Our findings reveal that sexual development relies on complex remodeling of peroxisomes and mitochondria, which is driven by their common fission machinery.